Subclinical onychomycosis in patients with type II diabetes - Amira Elbendary; Amira El Tawdy; Naglaa Zaki; Mostafa Alfishawy; Amr Rateb (PAGEPress Publications, 2015)
Fungal organisms could be present in the nail without any clinical manifestations. As onychomycosis in diabetics has more serious complications, early detection of such infection could be helpful to prevent them. We aim in this study to assess the possibility of detecting subclinical onychomycosis in type II diabetic patients and addressing possible associated neuropathy. A cross sectional, observational study included patients with type II diabetes with normal big toe nail. All were subjected to nail clipping of the big toe nail, followed by staining with Hematoxylin and Eosin and Periodic-Acid-Schiff (PAS) stains and examined microscopically. A total of 106 patients were included, fungal infection was identified in eight specimens, all were uncontrolled diabetes, and six had neuropathy. Using the nail clipping and microscopic examination with PAS stain to detect such subclinical infection could be an applicable screening test for diabetic patients, for early detection and management of onychomycosis.